Intracellular calcium promotes radioresistance of non–small cell lung cancer A549 cells through activating Akt signaling - Yiling Wang; Jiantao He; Shenghui Zhang; Qingbo Yang (Tumor Biology, 2017)
Radiotherapy is a major therapeutic approach in non–small cell lung cancer but is restricted by radioresistance. Although Akt signaling promotes radioresistance in non–small cell lung cancer, it is not well understood how Akt signaling is activated. Since intracellular calcium (Ca 2+ ) could activate Akt in A549 cells, we investigated the relationship between intracellular calcium (Ca 2+ ) and Akt signaling in radioresistant A549 cells by establishing radioresistant non–small cell lung cancer A549 cells. The radioresistant cell line A549 was generated by dose-gradient irradiation of the parental A549 cells. The cell viability, proliferation, and apoptosis were, respectively, assessed using the cell counting kit-8, EdU labeling, and flow cytometry analysis. The phosphorylation of Akt was evaluated by Western blotting, and the intracellular Ca 2+ concentration was assessed by Fluo 4-AM. The radioresistant A549 cells displayed mesenchymal morphology. After additional irradiation, the radioresistant A549 cells showed decreased cell viability and proliferation but increased apoptosis. Moreover, the intracellular Ca 2+ concentration and the phosphorylation level on the Akt473 site in radioresistant A549 cells were higher than those in original cells, whereas the percentage of apoptosis in radioresistant A549 cells was less. All these results could be reversed by verapamil. In conclusion, our study found that intracellular Ca 2+ could promote radioresistance of non–small cell lung cancer cells through phosphorylating of Akt on the 473 site, which contributes to a better understanding on the non–small cell lung cancer radioresistance, and may provide a new target for radioresistance management.